2022
DOI: 10.3389/fchem.2022.984131
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional exosomes derived from bone marrow stem cells for fulfilled osseointegration

Abstract: Bone marrow mesenchymal stem cells (BMSCs) have self-renewal, multi-directional differentiation potential, and immune regulation function and are widely used for de novo bone formation. However, the wide variation in individual amplification, the potential risk of cancer cell contamination, and the need for culture time significantly limit their widespread use clinically. Alternatively, numerous studies have shown that exosomes secreted by BMSCs in the nanoscale can also affect the functionality of endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…8 Exosomes made from stem cells, for example, can be used in cell-free therapies and have advantages over using actual stem cells, including not inducing an immune response against them, lowering the risk of thromboembolism, and evaluation in line with pharmacological agents. 13,25,26 Exosomes can control and have an impact on cell death throughout the network repair process. Because SPM exosomes include proteins that can control M1/2 macrophage polarization, they are effective at enhancing the quality of tendon/ligament integration into bone.…”
Section: Discussionmentioning
confidence: 99%
“…8 Exosomes made from stem cells, for example, can be used in cell-free therapies and have advantages over using actual stem cells, including not inducing an immune response against them, lowering the risk of thromboembolism, and evaluation in line with pharmacological agents. 13,25,26 Exosomes can control and have an impact on cell death throughout the network repair process. Because SPM exosomes include proteins that can control M1/2 macrophage polarization, they are effective at enhancing the quality of tendon/ligament integration into bone.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ncRNAs are present in exosomes that perform diverse functions including bone remodeling and bone-related disease [ 102 ]. BMSCs, osteoclasts, osteoblasts, lymphocytes, and macrophages secrete exosomes that regulate bone metabolism [ 103 ]. In bone metabolism, osteoblast differentiation is intercepted by exosomes secreted by osteoclasts [ 104 ].…”
Section: Exosomal Ncrnas and Bone Stem Cellsmentioning
confidence: 99%
“…Firstly, the efficacy of BMSCs in cell therapy depends on their ability to homing and long-term implantation into the injured site. The contribution of BMSCs in promoting new angiogenesis has been confirmed in animal models, but human clinical trials are not widely applied ( Zhuang et al, 2022 ). Previous reports showed that the number of CD34 + , C-kit + , or Flk-1 + cells, and the markers of endothelial lineage cells had increased in the wound healing process after the treatment of BMSCs conditioned medium ( Wu et al, 2007 ).…”
Section: Current Treatment Strategies For Iuamentioning
confidence: 99%